Design of Auxiliary Facilities to Reduce Potential Musculoskeletal Disorders in the Product Packaging Process - Dewa, Parama Kartika; Dewi, Novita (International Journal of Artificial Intelligence Research, 2023)
The manufacturing sector continues to grow after the Covid-19 pandemic. One of the competitiveness that supports the development of this sector is a business engaged in the packaging process. Several research studies show that packaging has a major influence on product marketability. However, not all packaging processes are managed by the product manufacturers themselves, but are left to other organizational partners. PBX is one of the organizations engaged in product packaging management. When carrying out the production process, operators experience complaints of musculoskeletal disorders, which have an impact on decreased performance and the risk of injury to operators. This is certainly a bad impact for the PBX. The REBA method is used to carry out analysis and efforts to improve work methods. This method was chosen because this method can help analyze potential injuries based on the operator's body when carrying out a work operation. The results obtained in the initial conditions of the worker's way of working, the operator's way of working is currently in the high risk category. This is indicated by the REBA value of 9. Improvement efforts to reduce this risk are carried out by using tools that can be used by operators. The results of the design improvement of assistive facilities can reduce high risk to low risk.